We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
50
3
avatar+865 

Prove this identity.

\(\frac{1+sin\theta}{1-sin\theta}=\frac{csc\theta+1}{csc\theta-1}\)

 May 1, 2019
 #1
avatar+100586 
+1

I'll use x instead of "theta"  [ easier to type.....LOL!!! ]

 

csc x + 1

_______    =

csc x -  1

 

 

1/sin x  + 1

_________  =

 1/sinx - 1

 

 

(1 + sin x ) / sinx

______________  =

(1 - sin x) / sin x

 

 

(1 + sin x)           sin x

________   *  ________  =

   sin x              1 - sin x

 

 

1 + sin x

________  =   the left hand side

1 - sin x

 

 

cool cool cool

 May 1, 2019
 #2
avatar+865 
+1

Can you start with the left side instead?

AdamTaurus  May 1, 2019
 #3
avatar+22188 
+2

Prove this identity.

\(\large \dfrac{1+\sin(\theta)}{1-\sin(\theta)}=\dfrac{\csc(\theta)+1}{\csc(\theta)-1}\)

 

\(\begin{array}{|rcll|} \hline && \dfrac{1+\sin(\theta)}{1-\sin(\theta)} \\\\ &=& \dfrac{1+\sin(\theta)}{1-\sin(\theta)}\cdot \dfrac{ \dfrac{1}{\sin(\theta)} } {\dfrac{1}{\sin(\theta)}} \\\\ &=& \dfrac{ \Big(1+\sin(\theta)\Big) \dfrac{1}{\sin(\theta)} } {\Big(1-\sin(\theta) \Big)\dfrac{1}{\sin(\theta)}} \\\\ &=& \dfrac{ \dfrac{1}{\sin(\theta)} + \dfrac{\sin(\theta)} {\sin(\theta)} } { \dfrac{1}{\sin(\theta)} - \dfrac{\sin(\theta)}{\sin(\theta)} } \\\\ &=& \dfrac{ \dfrac{1}{\sin(\theta)} + 1 } { \dfrac{1}{\sin(\theta)} - 1 } \quad | \quad \boxed{\dfrac{1}{\sin(\theta)} = \csc(\theta) } \\\\ &=& \dfrac{ \csc(\theta) + 1 } { \csc(\theta) - 1 } \\ \hline \end{array}\)

 

laugh

 May 2, 2019

9 Online Users